ProDiVis: a method to normalize fluorescence signal localization in 3D specimens - Nguyen, Kyle T.; Sathler, Alexandre R.; Estevez, Alvaro G.; Logan, Isabelle E.; Franco, Maria Clara (Frontiers in Cell and Developmental Biology, 2024)
A common problem in confocal microscopy is the decrease in intensity of excitation light and emission signal from fluorophores as they travel through 3D specimens, resulting in decreased signal detected as a function of depth. Here, we report a visualization program compatible with widely used fluorophores in cell biology to facilitate image interpretation of differential protein disposition in 3D specimens. Glioblastoma cell clusters were fluorescently labeled for mitochondrial complex I (COXI), P2X7 receptor (P2X7R), β-Actin, and DAPI. Each cell cluster was imaged using a laser scanning confocal microscope. We observed up to ~70% loss in fluorescence signal across the depth in Z-stacks. This progressive underrepresentation of fluorescence intensity as the focal plane deepens hinders an accurate representation of signal location within a 3D structure. To address these challenges, we developed ProDiVis: a program that adjusts apparent fluorescent signals by normalizing one fluorescent signal to a reference signal at each focal plane. ProDiVis serves as a free and accessible, unbiased visualization tool to use in conjunction with fluorescence microscopy images and imaging software.